The effect of peer education program on knowledge about menarche among students in elementary school: A quasi experimental study - Morita, Kriscillia Molly; Rustam, Junaidy Suparman (Nurse Point: Journal of Nursing, 2025)
Background: Adolescents often lack information about menarche due to general unawareness. The Indonesian Ministry of Health (2018) reports that the average age of menarche in Indonesia is 12.4 years, with a 60% prevalence rate. Many feel anxious and embarrassed about the physical changes, mainly due to a lack of knowledge. Purpose: This research aimed to assess the impact of a Peer Education Program on menarche knowledge among students at SD Negeri 09 Belakang Balok Bukittinggi in 2022. Methods: The study employed a quasi-experimental design with a nonequivalent control group from July to August 2022. The participant population included students from SD Negeri 09 Belakang Balok, who made up the experimental group, while students from SD Negeri 07 Belakang Balok served as the control group. Fifty respondents were selected using a purposive sampling technique, ensuring an equal distribution between the experimental and control groups. For data analysis, paired sample t-tests and independent sample t-tests were used to assess the impact of the intervention. Results: Results from the paired t-test revealed a p-value of 0.000 (p < 0.05), indicating a significant difference in the mean knowledge between the pre-test and post-test scores for both groups. Furthermore, the independent t-test results also yielded a p-value of 0.000 (p < 0.05), leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho). This confirms that the Peer Education Program significantly affected students' knowledge of menarche. Conclusion and recommendation: In conclusion, the Peer Education Program improved menarche knowledge among SD Negeri 09 Belakang Balok Bukittinggi students. It is recommended that schools incorporate this initiative into health education.